A Rare Case of Conjoined Pygopagus Twins: Case Report - Saputro, Christina; Siti Nurdiati, Detty; Taufiqur Rachman, Irwan (Nusantara Medical Science Journal, 2023)
Introduction and importance: Conjoined twins are a complication of monozygotic pregnancies with an incidence of 1:50,000-200,000 of life births. Pygopagus is found around 17% of all types of conjoined twins and has a mortality rate of 23%. Proper diagnosis and management in this case is important. Presentation of case: A 25-year-old primigravida woman presented at 22 weeks of gestation with a Pygopagus ultrasound result at 17 weeks of gestation. MRI was performed at 25 weeks of gestation, showed conjoined pygopagus twins with lumbosacral spina bifida, without visualized bone union, separated bladder, rectum and anus were difficult to evaluate. Caesarean section (CS) is planned at 36 weeks of gestation and postpartum MRI will be performed in preparation for the separation surgery. The patient was admitted to the hospital at 35 weeks of gestation in the active phase of the first stage of labor, then an urgent caesarean section was performed. Both babies were born with an APGAR score of 2/4/7. The second baby died a few hours after delivery. The separation surgery was performed as an emergency, but the first baby died during the procedure. Conclusions: Pygopagus requires holistic management, starting from diagnosis, preparation for delivery, to postpartum complications. The proper holistic management is expected to reduce infant and maternal morbidity and mortality.